(untitled) (London Journal of Research In Humanities and Social Sciences, 2023)
Community development entails inclusive change-making actions that include an appraisal of the community’s social, economic, and political status. It is built on a number of principles including engagement, dialogue, problem identification, finding the best solution within society, and capacity building for empowerment and consciousness rising. The impact of many central and state government, panchayath, and NGOs projects and schemes are transforming the Indian villages. Agrarian areas, which are the main focus of development, are undergoing significant changes as a result of government initiatives like land reform, electrification, irrigation, public distribution system, rural infrastructure, commercialization and monetization of various sectors of economic life, and unification of the nation through the development of communication means. 18 percent of the GDP is attributable to agriculture and allied sector, while 46 percent of Indians are directly employed in the agriculture sector. India won’t advance until its villages are improved. In order for Indian communities to grow, social or community workers must take a significant part in that process. Based on my own experience working on numerous rural development projects in Indian villages, the development approaches are to include communities in helping to promote and provide local programs.